Experimental investigation on friction coefficient and wear under different normal loads and sliding speed for different materials pairs - Bougoffa, Mohammed Seyf Eddine; Sayah, Tahar (University of Eloued جامعة الوادي, 2018)
In the present research, friction coefficients of different materials pairs are investigated and compared. Using CSM tribometer. Experiments are carried out when different types of samples such as aluminum and brass slide on steel pin. Experiments are conducted at normal load 3,5,8 and 10 N, sliding velocity 0.24, 0.35 and 0.48 m/s. Variations of friction coefficient with the duration of friction at different normal load and sliding velocity are investigated. Results show that the friction coefficient decreases with the increase of normal load and sliding velocity for all the tested pairs. On the other hand It is also found that the mass loss increase with the increase of normal load and sliding velocity.
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: Friction coefficient, Normal load, Sliding velocity, Mass loss